COOPER AND THE LITERARY DISCOVERY OF THE SEA - Philbrick, Thomas (Canadian Review of American Studies, 1989)
It comes as something of a shock to those who return to Cooper in maturity to find that eleven of his thirty-two works of fiction are full-fledged novels of the sea, books in which the characters are not hunters, squatters, Indians and soldiers, but merchant seamen, sealers, man-of-war's men, packet masters and pirates. Their settings are not frontier settlements like Templeton or wilderness outposts like Fort William Henry, not the forest or the prairie, but Narragansett Bay, New York Harbor, the English Channel and the Straits of Sunda. They are informed not by the lore of the hunt and the warpath but by the technology of seamanship and the principles of naval tactics. The areas of nautical experience with which they deal are so diverse that together they comprise a virtual microcosm of the great world of maritime activity in the eighteenth and nineteenth centuries. Cooper's accounts of colonial smuggling, Caribbean piracy, the China trade, the Antarctic seal fishery and the transatlantic packet service supply a vivid informal history of American nautical enterprise. He extends his range to European maritime experience in two of these novels: The Wing-and-Wing tells the story of a French privateer in the Mediterranean during the Napoleonic wars, while The Two Admirals carries its readers back to the mid-eighteenth century and the complex fleet actions of the Royal Navy.